Ethnoscience Study of Sedekah Bumi Bangsri Jepara Village in Elementary School Science Subjects - Nandia, Fira; Sayekti, Ika Candra (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
The rapid flow of globalization can threaten the fading of local cultural values in Indonesia. This can be a challenge for the Indonesian people to choose between maintaining or eliminating the existing environmental culture. Therefore, an approach is needed, namely ethnoscience in the learning process. This study aims to describe the ethnoscience of Sedekah Bumi in Bangsri Jepara Village in elementary science material. The method used is qualitative with a phenomenology research design. The subject of this research was village heads and village officials. The data was obtained by observation, interview, and documentation. Data validation was conducted through triangulation. Based on the research results, it is known that ethnoscience learning can be integrated into elementary science learning, as evidenced in every series of almsgiving activities in Bangsri Jepara Village, including ingkang damar murup, colossal dance, shadow puppets, buffalo slaughter, and the penjor Â festival. Based on the research that has been done, it is concluded that science content is integrated into grade III, IV, and V SD materials. Grade III material that is integrated with the alms of the earth is a change in the form of objects and the benefits of plants for humans. Grade IV material is the style of motion, the relationship between form and function of animal and plant body parts, and light. Grade V materials are heat transfer, human organs, and the classification of animals based on the type of food they eat. Then, in addition to SD material, namely the emulsion in coconut milk and nutrients in the soil in plants. It is hoped that this research will not only be able to integrate the Sedekah Bumi culture with elementary science material but that students can also relate the almsgiving culture with cultural preservation activities